1954
DOI: 10.1515/znb-1954-0715
|View full text |Cite
|
Sign up to set email alerts
|

Notizen: Zur Kenntnis eines Bortriazids B(N3)3

Abstract: Borwasserstoff setzt sich in ätherischer Lösung mit Stickstoffwasserstoffsäure gemäß der GleichungBH3 + 3 HN3→B(N3)3 + 3 H2unter Bildung eines im hexagonalen System kristallisierenden, im Hochvakuum flüchtigen, ätherlöslichen, feuchtigkeits-empfindlichen, farblosen, hochexplosiven Borazids B(N3)3 um, das die bis jetzt nur durch das Bornitrid BN vertretene Klasse der Bor-Stickstoff-Verbindungen um ein sehr stickstoffreiches Glied BN9 (92,1% N) bereichert. Mit Lithium- und Natriumazid vereinigt sich das Borazid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…[60] Later, this Lewis acid was prepared in a safer way by treatment of aluminum chloride with sodium azide in THF. [60] Later, this Lewis acid was prepared in a safer way by treatment of aluminum chloride with sodium azide in THF.…”
Section: Methods Using Lewis Acidsmentioning
confidence: 99%
“…[60] Later, this Lewis acid was prepared in a safer way by treatment of aluminum chloride with sodium azide in THF. [60] Later, this Lewis acid was prepared in a safer way by treatment of aluminum chloride with sodium azide in THF.…”
Section: Methods Using Lewis Acidsmentioning
confidence: 99%
“…Beryllium azides tend to form predominantly ionic bonds, but are also expected to show covalent bonding contributions owing to the small size of the Be 2+ ion and its high charge density.However,even though Be(N 3 ) 2 [1] and solvent-coordinated beryllium azide complexes L 2 Be(N 3 ) 2 (L = THF,p yridine) [2] have been synthesized, their solid-state structures are unknown. Only two heteroleptic beryllium azides [Ph 4 )-[(C 12 H 26 N 2 )BeCl(N 3 )]) have been structurally characterized.…”
mentioning
confidence: 99%
“…[1,2] Tw oa dditional resonances were observed in both spectra at À131 and À276 ppm, which are due to the presence of free N 3 À ( Figure S32). [12] As decomposition reactions can be excluded in [D 6 ]DMSO,weperformed temperature-dependent 9 Be and 14 NN MR experiments with 2.T he 14 NN MR spectra clearly showed the existence of an equilibrium in solution that is fully temperature-reversible (Figure 1).…”
mentioning
confidence: 99%
“…In recent years, group III azides have attracted considerable interest for their potential use as candidates for high energy density materials (HEDMs) . Boron triazide, B(N 3 ) 3 , has been known for nearly 60 years, since it was firstly synthesized in 1954 by the reaction of diborane with HN 3 in an ether solution at low temperature by Wiberg and Michaud . In 1995, Mulinax et al reported gas‐phase synthesis boron triazide by a spontaneous room temperature reaction between HN 3 and BC1 3 .…”
Section: Introductionmentioning
confidence: 99%